Penyuluhan Pupuk Organik Untuk Meningkatkan Kesuburan Tanah Guna Mencapai Kemakmuran di Desa Pandankrajan Kecamatan Kemlagi - Khoirul Anam; Devanka Tegar Perdana P; Yusla Issabella Valentina; Valencya Refesga Lentera; Maulina Salsabila Virginisa; Intan Maharani; Ris Karima Enjelina; Abdul Aziz Fhad Haidar A; Akhmad Johan Adam J; Lenterana Wandahan Mustofa; et al. (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
Organic fertiliser is fertiliser derived from dead plants, animal manure or animal parts and organic waste that has gone through an engineering process, in the form of solid or liquid, rich in mineral and microbial materials, useful for increasing soil nutrient content and improving physical, chemical and biological properties of soil. Increase soil nutrient content and improve soil physical, chemical, biological properties. Organic fertilisers undergo a phase of decomposition by soil microorganisms so that the nutrients are absorbed by plants and the rest becomes humus. Its use provides long-term benefits, including forming ions and nutrients that are easily absorbed by plant roots, releasing soil nutrients slowly and sustainably so as to help prevent nutrient supply explosions that cause plant poisoning, helping to maintain soil moisture, reducing soil structure pressure on plant roots, increasing the stability of soil particle composition so as to facilitate the movement of water and air particles in the soil, facilitating the activity of good microorganisms, and increasing root and seed growth. This community service programme in Pandankrajan Village has demonstrated strategies to increase the selling value of agricultural production, which will benefit farmers by increasing their income.